A Project Report on Implementation of Biometric System in Digital Cameras - KANJANAVA GHSOH, BIKRAMJIT SHARMA and AYUSH AGARWAL (2015)
INTERNAL GUIDE: MR VINAY REDDY, MVJCE
Keywords: Biometric System in Digital Cameras